Frequency of a state of cloud systems over tropical warm ocean - Kumar, Shailendra (2019)
The knowledge of how long a mesoscale convective system stays in a given stage of life cycle is an important information for many practical applications. A unique approach has been adopted here to find the stage of development of convective cloud systems (CCSs) over tropical oceanic areas. We use the Tropical Rainfall Measuring Mission (TRMM) data products, and define a cloud system (CS) based on criteria that depend on TRMM precipitation radar equivalent radar reflectivity factor (Zₑ) and TRMM Microwave Imager polarization corrected temperature data. Average vertical profile of Zₑ and convective area fraction (CAF) of a CS are used to identify its state which is a proxy for life stage. We use two parameters, namely reflectivity differences (RD) and convective area fraction (CAF) and defined 5 states of CS life cycle. Our results show that majority of CSs are found in mature stage and formative and dissipation stages are relatively short over the twelve warm tropical oceanic areas selected for analysis. Each ocean has a distinct signature in the RD-CAF phase space, and, there are regional/seasonal differences within an ocean basin. Bay of Bengal has less CAF compared to the equatorial Indian ocean. In the tropical Pacific Ocean, majority of the CSs lie in mature stage with CAF between 0.3 to 0.6, whereas, CSs in mature stage over the Atlantic Ocean have their CAF between 0.2 and 0.3. CS characteristics over the Atlantic Ocean during the Boreal summer and winter are different.